Analisis Perbandingan KBK (Kurikulum Berbasis Kompetensi), KTSP (Kurikulum Berbasis Sekolah), dan Kurikulum 2013 - Sugianto, Riris (YASIN, 2022)
This study aims to discuss the comparison between KBK, KTSP and Curriculum 2013 where there are many criticisms of the government's proposal to radically change the elementary school curriculum into six subjects: mathematics, Indonesian language, religious studies, Pancasila, sports, and arts. However, critics have put forward some very weak arguments and fail to see how the proposed curriculum will help Indonesia – far more effectively than it currently is – build a first-class education system. One good a priori reason to think that the government is right and the critics wrong is that the proposed curriculum is very similar to the curriculum taught in primary schools in England and is universally admired in education circles around the world. The reason why basic English education is so admired for wanting a basic education: to develop children's curiosity and curiosity and encourage critical thinking and creativity by not burdening them with too many set subjects but using the available time to integrate teaching according to various topics. In classes where children are ostensibly studying mathematics or English or religion or art, they are at the same time exposed to knowledge of the world around them and their social and physical environment, a broad understanding of specific periods in history. , moral ideas, and awareness of their own potential. All of this takes place in a context where children learn to take responsibility for their own learning through discovery and investigation, reading, asking questions, watching video clips, utilizing IT resources, libraries, and educational classroom aids (CW Watson, 2012).